Ethical and Fair Work Behaviour: A Normative-Empirical Dialogue Concerning Ethics and Justice - Singer, M. S. (Journal of business ethics, 2000)
Towards the general goal of generating a normative-empirical dialogue about ethics and justice, the present study explored three issues: (1) the extent to which the normative criteria of ethics and justice prescribed by moral philosophers are indeed reflected in managerial professionals' subjective beliefs of what ethical and just work behaviour ought to be, (2) the relationship between people's ought beliefs and their perceptions of actual ethical and just work behaviour, and (3) the relationship between the notions of ethics and justice. To do so, a review of the normative and positive theories of ethics was carried out which revealed the key normative criteria of ethics (i.e., utility, rights, justice, principle and care) and justice (i.e., due procedure and due outcome). Using both the interview and the repertory grid procedures, key determinants of ethical and just work behaviour as perceived by the managerial professionals were generated. These determinants were used to construct the questionnaires for the assessment of people's subjective ought beliefs, and their is judgements, of ethical and just work behaviour. There were three respondent samples: managerial professionals, general public and university students. Results showed that (1) people's subjective ought beliefs closely reflected the normative standards of ethics and justice, (2) there were significant discrepancies between people's subjective ought beliefs and their perceptions of actual ethical and just work behaviour, (3) individual differences in ought beliefs had some influence on is judgements, (4) both the ought beliefs and is judgements pertaining to the notion of justice could be accounted for by measures of the other four criteria of ethics and in particular, the notion of rights. The implications of the findings for normative theories of ethics and for ethics education are discussed.